Tiktok Social Media-Based Marketing Strategy to Increase MSMEs Product Sales Among Students in the Industrial Revolution Era 4.0 - Mifta Meylinda; Ima Setiani; Dini Syafitri; Sabila Henfi Amalia (CV Media Inti Teknologi, 2023)
The background of the research that has been carried out is to find out whether the social media-based marketing strategy of Tiktok is able to increase product sales. This research is a research that uses a descriptive research model with a qualitative and quantitative approach. What was examined in this study was a marketing strategy to increase sales of MSMEs products in the form of a bouquet of wire bristles. This study aims to determine the effectiveness of using social media tiktok as a marketing medium to increase sales. The data collection instruments used in this study were direct observations (interviews) and questionnaires. Data collection and data analysis in the form of observations are carried out by providing two stages to find out whether the sales strategy of using social media is effective in increasing sales results or not. The results of the analysis of several respondents stated that offline store sales alone were not effective in product marketing. Thus knowledge is needed about the description of marketing strategies by utilizing social media, one of which is TikTok to increase product sales. This is because there are so many tiktok users, both from teenagers to adults. In addition, product marketing has a wider target market.